Impacts of attitude towards online banner advertisement on brand awareness: insight from persuasive hierarchy model - S. Busen, Salem Mohamed; Mustaffa, Che Su; Mohamad, Bahtiar (MCSER Publishing, Rome-Italy, 2016)
Researchers have noted that the visible progress of online advertising is not as actual as compared to the substantial amount of effort and resources advertisers have devoted into advertising through the digital medium.In view of these challenges, attention has been drawn to the need to examine the role of the dynamism of the antecedents which shape the awareness and performances of brand particularly in the Arab world. Therefore, based on this study's review, the importance and impacts of attitude towards online banner advertisements as an antecedents were identified. Similarly, in situating the antecedent within the model of persuasive hierarchy framework the study was able to explain the impact of awareness on brand performance.In conclusion, the study reviews have highlighted the significance of information on where online banner advertising campaigns should focus, which in turn affords for successful brand.